Alterations of m6A RNA methylation regulators contribute to autophagy and immune infiltration in primary Sjögren’s syndrome - Cheng, Linlin; Li, Haolong; Zhan, Haoting; Liu, Yongmei; Li, Xiaomeng; Huang, Yuan; Wang, Li; Zhang, Fengchun; Li, Yongzhe (Frontiers in Immunology, 2022)
N6-methyladenosine (m6A) RNA modification is a new epigenetic regulation mechanism on eukaryotic mRNA. Few autoimmune diseases focused on the role of m6A in their pathogenies, and m6A modulation in the pathological process of primary Sjögren's syndrome (pSS) is still unknown. In this work, three microarray datasets of pSS patients were downloaded from the GEO database: dataset #1 and #2 from the whole peripheral blood (PB) samples, dataset #3 from the labial salivary gland tissue samples, as well as a PB cohort collected from our hospital. Six differentially expressed m6A regulators were identified by comparing the PB dataset #1 of pSS and healthy controls using the Wilcox test and logistic regression analysis. Among them, 4 (ALKBH5, RBMX, RBM15B and YTHDF1) were confirmed as down-regulated in the PB dataset #2 and in our PB cohort by RT-PCR, and 4 (ALKBH5, METTL3, RBM15B, and YTHDF1) were confirmed as down-regulated in the dataset #3 of the labial gland tissue. In addition, discrepantly expressed m6A regulators accompanied by diverse immunocytes, including dendritic cells (DCs), T cells, and CD56dim natural killer cells, and among the regulators, ALKBH5 and METTL3, were comprehensively linked with the infiltrated immune cells. Notably, the most enriched autophagy mechanism mediated by m6A was observed in pSS using functional annotation analysis. Ten hub genes were identified using a protein–protein interaction network, and their expression in the PB dataset #2 and the expression of 3 genes (PIK3CA, STAT1, and MAPK3) in the labial gland tissue dataset #3 were confirmed. Our study provides the evidence that m6A methylation is widely involved in the immune infiltration and autophagy of pSS, thus contributing to the pathogenesis of this disease and potentially representing a novel therapeutic target.